2017
DOI: 10.1007/s10661-017-5895-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity assessment of a West Virginia chemical spill mixture involving 4-methylcyclohexanemethanol and propylene glycol phenyl ether

Abstract: Thousands of gallons of industrial chemicals, crude 4-methylcyclohexanemethanol (MCHM) and propylene glycol phenyl ether (PPh), leaked from industrial tanks into the Elk River in Charleston, West Virginia, USA, on January 9, 2014. A considerable number of people were reported to exhibit symptoms of chemical exposure and an estimated 300,000 residents were advised not to use or drink tap water. At the time of the spill, the existing toxicological data of the chemicals were limited for a full evaluation of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The first responders in this case relied on the chemical company responsible for the spill to accurately disclose the nature of the contamination and then screened large numbers of samples only for the reported contaminant. When accurate information was not forthcoming until several days after the initial contamination event, residents were inadvertently exposed to additional contaminants, first responders were unable to develop effective remediation strategies, and the development of an effective containment response was delayed . Similar gaps in current state-of-the art detection methods explain why consumers were initially unaware of the presence of bisphenol A (BPA) analogues, including bisphenol S (BPS) and bisphenol F (BPF), in the presence of products labeled “BPA-free,” and were inadvertently exposed to these BPA derivatives .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first responders in this case relied on the chemical company responsible for the spill to accurately disclose the nature of the contamination and then screened large numbers of samples only for the reported contaminant. When accurate information was not forthcoming until several days after the initial contamination event, residents were inadvertently exposed to additional contaminants, first responders were unable to develop effective remediation strategies, and the development of an effective containment response was delayed . Similar gaps in current state-of-the art detection methods explain why consumers were initially unaware of the presence of bisphenol A (BPA) analogues, including bisphenol S (BPS) and bisphenol F (BPF), in the presence of products labeled “BPA-free,” and were inadvertently exposed to these BPA derivatives .…”
Section: Discussionmentioning
confidence: 99%
“…When accurate information was not forthcoming until several days after the initial contamination event, residents were inadvertently exposed to additional contaminants, first responders were unable to develop effective remediation strategies, and the development of an effective containment response was delayed. 1845 Similar gaps in current state-of-the art detection methods explain why consumers were initially unaware of the presence of bisphenol A (BPA) analogues, including bisphenol S (BPS) and bisphenol F (BPF), in the presence of products labeled "BPA-free," and were inadvertently exposed to these BPA derivatives. 1846 Detection methods for BPA relied on mass spectral methods; 1847 because the BPA analogues have slightly different molar masses, they remained undetected in the products for an as-yet undetermined amount of time.…”
Section: Discussionmentioning
confidence: 99%
“…Crude MCHM is not a dermal irritant to humans at the concentrations in the water reported after the spill [7]. In the evaluation of different cell lines, HEK-293, HepG2, H9c2, and GT1-7 only the highest dose of MCHM (128 ppm or 1 mM) elicited a statistically significant decrease in cell viability, when compared to the control (1% DMSO) [8]. MCHM induced DNA damage-related biomarkers in human A549 cells, indicating that it is related to genotoxicity [9].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that amino acids [32], inositol [32], zinc [27], and phosphate [27] levels are increased. Since the 2014 MCHM spill, several studies have measured the toxicological effects of MCHM on diverse species but have not addressed the mechanism of toxicity during acute exposure [64][65][66][67][68][69][70][71]. One possible explanation of MCHM's diverse effects is, as a stable hydrotrope, MCHM changes the structure of nutrient sensors so they no longer sense extracellular compounds.…”
Section: Discussionmentioning
confidence: 99%